Implementation of Light Steel Roof Design in Gili Iyang Ubhara Sumenep - Wa’idul Hasan; Aditya Dandy Firatama (Universitas Islam Raden Rahmat, Malang, 2026)
The increasing demand for housing in Indonesia requires innovative and efficient construction systems to ensure sustainable development. This study presents the design and analysis of a lightweight steel roof structure, tittled “Gili Iyang Ubhara,” inspired by the ecological values of Gili Iyang Island in Sumenep, known for its exceptional air quality. The design integrates the concept of a green and solar roof to optimize energy use and environmental performance. The structural analysis methodology used in this research is standards of SNI 7971:2013 and SNI 1727:2020. The roof structure was then analyzed with SAP2000 software to evaluate strength, load distribution, and material efficiency. The results show that all members of the structure have strength ratios below 1.0, indicating safe performance under dead, live, and wind loads. The combination of solar panels and green roof elements contributes to reduced heat absorption and increased energy efficiency. For the record, future research is recommended to incorporate dynamic thermal–energy simulations to quantify the long-term performance of hybrid eco-roof systems under varying climatic conditions, thereby enhancing predictive accuracy for large-scale implementation.